1. The problem statement, all variables and given/known data Find the general solution of 2y(x^3+1)dy + 3x^2(1-y^2)dx = 0 2. Relevant equations 3. The attempt at a solution So I first grouped the terms with dy or dx 2y/(1-y^2) dy = -3x^2/(x^3 +1) dx after integrating both sides and solving, I got ln (1-y^2)= -ln(x^3 +1) + c and then after simplifying, it becomes 1-y^2= A/(x^3 + 1) and therefore y^2= -A/(x^3+1) + 1. The answer according to the book was y^2= 1 + A(x^3 +1). How did they get that?? Maybe if i could get rid of the negative sign for ln, it might help....but please if u can help me, it would be appreciated. Thanks.